Main drivers in agricultural research and education to secure food supply and assure sustainability - Mínguez M.I.; Connor D.J. (Agricultural higher education in the 21st century : a global challenge in knowledge transfer to meet world demands for food security and sustainability, 2015)
The growing world population, 9.8 billion by 2050, and increasing affluence are placing ever greater pressures on agriculture to feed the world well (a 70% increase in production is projected) while conserving as much of natural systems and their resources as possible for other purposes. The result is a focus on (ecological or sustainable) intensification of agricultural production, i.e. the greater inputs of science and technology needed to produce more crop and animal products per unit area per year while restricting deleterious off-site impacts of agriculture, including emissions of greenhouse gases (GHG). Markets will always play a fundamental role in food security notwithstanding that price volatility that was at the base of the food crisis of 2008, could happen again. Farms which are the production units must be sustainable, and their sustainability relies on economic, social and environmental performance. There are no magic bullets. Agricultural production is a stoichiometric process. The harvesting of grains and meat extract nutrients from soils and must be replaced for continuing productivity. The solution to intensification is found in more and better scientific understanding of agricultural production and technological applications as aids to management. For high productivity, crops and flocks need continuous attention to growth and reproduction and to the control of pests and diseases that are the greatest threat to productivity. External thermal environments cannot be improved for crop and animal growth so success is found in selection and management of adapted farming systems. Water shortage is a common limitation to productivity in many regions. Globally, crop (arable) land amounts to 1500 Mha of which just 300 Mha are irrigated. The scope for expansion of irrigation is limited because both land and water resources are fiercely contested for other uses.
International Conference : Agricultural Higher Education in the 21st Century, 2015/06/15-17, Zaragoza (Spain)